Change management on digital transformation in vehicle tax payment process: An understanding from institutional analysis - Helga Rini Fadhina; Nurul Fauzi; Eka Siskawati; Muhammad Rizky Prima Sakti; Nazliatul Aniza Abdul Aziz (International Ecsis Association, 2022)
Although the application of new technologies in an organization is very challenging, changes in the external environment must be responded by the organization in order to survive in the midst of business competition. The implementation of new technologies must be accompanied by changes in the internal culture and the readiness of management organization. Motor vehicle tax is the largest source of state revenue in the West Sumatra region. The implementation of the advanced digital technology in vehicle payment process (SIGNAL technology) is a government strategy in an effort to increase the effectiveness and accountability of the motor vehicle tax payment process. This paper analyzes the dynamics of change management in the One-stop Administration Services (SAMSAT) office of west sumatra province during the adoption of SIGNAL technology. This study used the qualitative approach, located in the SAMSAT office in West Sumatra. The choice of informants through purposive sampling techniques. Data collection techniques are observation, interviews, and documentation analyzed through data reduction, data presentation, verification, and conclusions. The results show that the government's readiness to face changes in the implementation of the motor vehicle tax payment application through the SIGNAL application for SAMSAT West Sumatra is good. In the sense that it is ready to implement the signal application. The obstacles faced when implementing the Signal application to increase motor vehicle tax revenues are in the form of attitudes of employees and leaders.